Review Perkembangan PLTS di Provinsi Bali Menuju Target Kapasitas 108 MW Tahun 2025 - Pawitra Putra, A.A. Gede Ari; Kumara, I.N.S.; Ariastina, W. G. (Majalah Ilmiah Teknologi Elektro; Vol 19 No 2 (2020): (Juli - Desember) Majalah Ilmiah Teknologi ElektroDO - 10.24843/MITE.2020.v19i02.P09, 2020)
The central government policy through RUEN targets Bali to use 108 MWp of solar energy by 2025. Bali as a small island of highly developed tourism destinations in Indonesia is considered to have the opportunity to exploit this potential. This research tries to review how the development of PV system in Bali through literature study and field observation. The results of this study indicate that the development of total PV system installed capacity in Bali to date has reached 3.71 MWp or 3.44% of the RUEN target. Based on data managed by the development of PV system in Bali in the last 14 years it increased an average of 265.18 kWp or 7.14% annually. Until now the highest PV system capacity in Bali is in Karangasem Regency which has an installed PV system capacity of 1,106 kWp or 29.79% of the total capacity in Bali. While the lowest capacity is in Jembrana Regency with an installed capacity of 10 kWp or 0.27%. PVsystem in Bali is used in a variety of applications, the largest capacity used for utilities is 58.64%, while the lowest is used for water pumps by 0.55%. Based on the type of PV system, Bali is dominated by an on-grid PV system with an installed capacity of 3,225 kWp or 87%, while the lowest is a hybrid PV system with a capacity of 224 kWp or 6% of the total capacity in Bali.